2022
DOI: 10.3390/molecules27061974
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial and Cytotoxic Activity of Novel Imidazolium-Based Ionic Liquids

Abstract: In this study, a series of 10 novel 1-methyl-3-octyloxymethylimidazolium derivatives carrying various anionic moieties (4-hydroxybenzenesulfonate, benzenesulfonate, carvacroloxyacetate, chloride, formate, propionate, thymoloxyacetate, vanillinoxyacetate, eugenoloxyacetate and trimethylacetate) were synthesized. Compounds were tested for their antimicrobial activity against six microbe strains (Staph-ylococcus aureus, Pseudomonas aeruginosa, Klebsiella pneumoniae, Escherichia coli, Enterococcus faecalis, and Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 49 publications
(58 reference statements)
1
7
0
Order By: Relevance
“…Pałkowski et al obtained novel 1-methyl 3-octyloxymethylimidazolium derivatives carrying various anionic moieties [ 141 ]. The basis for the syntheses were the few scientific reports on the anticancer activity of ionic liquids [ 142 , 143 ].…”
Section: The Most Potent Anti-melanoma Agent From Most Recent Studies...mentioning
confidence: 99%
See 1 more Smart Citation
“…Pałkowski et al obtained novel 1-methyl 3-octyloxymethylimidazolium derivatives carrying various anionic moieties [ 141 ]. The basis for the syntheses were the few scientific reports on the anticancer activity of ionic liquids [ 142 , 143 ].…”
Section: The Most Potent Anti-melanoma Agent From Most Recent Studies...mentioning
confidence: 99%
“…Compound (57) exhibited the most promising activity against melanoma cell line B16F10 with IC 50 = 1.01 × 10 −2 µM/L. The most active derivative bore the thymoloxyacetic anion [ 141 ].…”
Section: The Most Potent Anti-melanoma Agent From Most Recent Studies...mentioning
confidence: 99%
“…It is noteworthy that, due to the ability to design the structure of multifunctional surface-active compounds, there has been a significant increase in interest in these compounds, especially owing to their use as antimicrobials [ 19 , 20 , 21 , 22 , 23 ]. For example, Shaheen et al [ 22 ] described SAILs in the context of their antimicrobial activity, similar to their quaternary ammonium counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Shaheen et al [ 22 ] described SAILs in the context of their antimicrobial activity, similar to their quaternary ammonium counterparts. Also, in our recent works, we discussed the role of imidazolium SAILs with high surface activity as a potential tool for destroying microbes [ 5 , 19 ]. Another important use of SAILs and surface-active QASs focuses on sectors such as agriculture.…”
Section: Introductionmentioning
confidence: 99%
“…Previous investigations mainly focused on the relationship between the chemical structure of ILs and their toxicity. Studies have indicated that the inhibition of bacterial growth by ILs is due to their affinity and disruptive effect of ILs on the cell membrane and cell wall ( Docherty and Kulpa, 2005 ; Cornmell et al, 2008 ; Busetti et al, 2010 ; Ventura et al, 2013 ; Ghanem et al, 2015 ; Zheng et al, 2016 ; Cook et al, 2019 ; Pałkowski et al, 2022 ). The cationic structure of ILs is key to their toxicity because it allows ILs to be easily adsorbed and enriched in the negatively charged cell walls of bacteria.…”
Section: Introductionmentioning
confidence: 99%